Correlation between defense mechanisms and style peculiarities of self-regulation in patients with depression - Truhan, Elena A.; Morozova, Natalia N.; Boud’ko, Tatyana O. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article discusses the results of comparative and correlation research defense mechanisms and style peculiarities of self-regulation in patients with depression and in healthy people. The mechanisms of regression, compensation, reaction formations and the general intensity of psychological defense are significantly higher in patients with depression. Programming, evaluation and the general level of self-regulation are significantly higher in healthy people. The mechanisms of denial and intellectualization increase the ability to self-regulation in healthy people and in patients with depression; repression, regression and compensation, on the contrary, decrease. The functioning of psychological defenses increases the regulatory independence of healthy people and of patients with depression, but makes it difficult to condition modeling, programming and evaluation of the results. The greatest number of significant correlations between defense mechanisms and programming was found in healthy people and in patients with depression. An inversely correlation between the general intensity of psychological defense and the general level of self-regulation was found only in patients with depression.